2020
DOI: 10.1002/lno.11423
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal constraints on the abundance and activity of the cyanobacterium UCYN‐A and other marine diazotrophs in the North Pacific

Abstract: The number of marine environments known to harbor dinitrogen (N 2)-fixing (diazotrophic) microorganisms is increasing, prompting a reassessment of the biogeography of marine diazotrophs and N 2 fixation rates (NFRs). Here, we investigate the diversity, abundance, and activity of diazotrophic microorganisms in the North Pacific Subtropical Gyre (NPSG), a diazotrophic habitat, and the North Pacific Transition Zone (NPTZ), a region characterized by strong physical, chemical, and biological gradients. Samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(92 citation statements)
references
References 115 publications
8
78
0
Order By: Relevance
“…In a non-metric multidimensional scaling (NMDS) analysis where each metabolite was treated with equal weight, there was a distinct shift in metabolite patterns in the samples on either side of approximately 30 • N ( Figure S2, ANOSIM stat = 0.316, p = 0.005). This corresponds well with the southern boundary of the North Pacific Transition Zone, a well described oceanographic feature which extends from Japan to North America and arises from large-scale ocean circulation (26,27). The northern and southern edges of this transition zone comprise of rapid changes in thermohaline structure and biological species composition (28,26,29).…”
Section: S Submission Template Msystems Submission Template Msystems supporting
confidence: 64%
See 1 more Smart Citation
“…In a non-metric multidimensional scaling (NMDS) analysis where each metabolite was treated with equal weight, there was a distinct shift in metabolite patterns in the samples on either side of approximately 30 • N ( Figure S2, ANOSIM stat = 0.316, p = 0.005). This corresponds well with the southern boundary of the North Pacific Transition Zone, a well described oceanographic feature which extends from Japan to North America and arises from large-scale ocean circulation (26,27). The northern and southern edges of this transition zone comprise of rapid changes in thermohaline structure and biological species composition (28,26,29).…”
Section: S Submission Template Msystems Submission Template Msystems supporting
confidence: 64%
“…-37.3 11.4-17.1 34.1-34.7 0.06-5.87 0.07-0.51 0.16-0.37 Summary of physical and chemical parameters on April 2016 cruise. Reprinted with permission from(27).…”
mentioning
confidence: 99%
“…While the domain of marine BNF has been broadened with ongoing studies and active BNF in the Arctic region (Harding et al, 2018; Shiozaki et al, 2018; Sipler et al, 2017), diazotrophs and BNF were found to be rare or absent in the NPTZ where constitutes approximately 12% of the surface area of the North Pacific Ocean (Church et al, 2008; Gradoville et al, 2020; Shiozaki et al, 2017). The most recent survey of diazotrophs in the NPTZ was conducted along latitudinal transects in the central Pacific along 160°W during spring (Gradoville et al, 2020), in which the diazotroph abundance decreased suddenly at the southern edge of the NPTZ (~32°N) and became rare or undetected in the NPTZ (~32–40°N). A similar study conducted along 170°W also found undetectable diazotroph abundance with qPCR and relatively low BNF in the NPTZ between 35 and 40°N (Shiozaki et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For most sample sets, complementary sequence data were available to determine whether UCYN-A2 or UCYN-A3 was present. This figure was modified from Farnelid et al 2016, and updated to include data from Hagino et al 2013, Shiozaki et al 2017, 2018, Stenegren et al 2018, Berthelot et al 2017, Henke et al 2018, Harding et al 2018, Gradoville et al 2020, and this work.…”
Section: Fig 1 Map Of Distribution Of Ucyn-a In the Pacific And Arcticmentioning
confidence: 99%